2021
DOI: 10.1038/s41467-021-25714-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D MAPs pipeline identifies the morphological sequence chondrocytes undergo and the regulatory role of GDF5 in this process

Abstract: The activity of epiphyseal growth plates, which drives long bone elongation, depends on extensive changes in chondrocyte size and shape during differentiation. Here, we develop a pipeline called 3D Morphometric Analysis for Phenotypic significance (3D MAPs), which combines light-sheet microscopy, segmentation algorithms and 3D morphometric analysis to characterize morphogenetic cellular behaviors while maintaining the spatial context of the growth plate. Using 3D MAPs, we create a 3D image database of hundreds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…The advances in elucidating a complete molecular regulatory network will rely on combining imaging, bio information, and genetic models. For example, Rubin et al developed an imaging and analysis pipeline, called 3D Morphometric Analysis for Phenotypic significance (3D MAPs), which creates 3D morphology maps of the growth plate by using a procedure to clear tissue, segment chondrocytes, and project cells onto their locations [ 92 ]. Three-dimensional MAPs revealed continuous morphogenetic behaviors of chondrocytes within the growth plate.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…The advances in elucidating a complete molecular regulatory network will rely on combining imaging, bio information, and genetic models. For example, Rubin et al developed an imaging and analysis pipeline, called 3D Morphometric Analysis for Phenotypic significance (3D MAPs), which creates 3D morphology maps of the growth plate by using a procedure to clear tissue, segment chondrocytes, and project cells onto their locations [ 92 ]. Three-dimensional MAPs revealed continuous morphogenetic behaviors of chondrocytes within the growth plate.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Over recent years, progress has been made in characterising the cellular dynamics involved in tissue growth. Spatial morphometric analyses were conducted on light-sheet images of the embryonic murine tibia, revealing that a number of cell morphological changes and growth strategies contribute to growth plates' expansion, especially highly spatially-dependent cell volume expansions [45].…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, progress has been made in characterising the cellular dynamics involved in tissue growth. Spatial morphometric analyses were conducted on light-sheet images of the embryonic murine tibia, revealing that a number of cell morphological changes and growth strategies contribute to growth plates’ expansion, especially highly spatially-dependent cell volume expansions [45]. Quantification of tissue growth based on cell lineage tracking data in the developing chick limb bud [46] and the Drosophilia wing disc [47] showed that spatially and temporally heterogeneous growth patterns coupled with growth anisotropy are major drivers of tissue morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research quantifying cellular dynamics involved in growth and morphogenesis using computational tools. Rubin et al (2021) Suzuki & Morishita, 2017;Tozluoglu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research quantifying cellular dynamics involved in growth and morphogenesis using computational tools. Rubin et al ( 2021 ) built 3D maps of cell morphologies from light‐sheet images of the embryonic murine tibia. Cell density, surface area, volume and orientation were quantified and spatially analysed revealing that differential cell volume expansion underlies tissue morphogenesis of the developing growth plates.…”
Section: Introductionmentioning
confidence: 99%